Surfactant-assisted assembly of nanoscale zinc coordination compounds to enhance tandem conversion reactions in water. Issue 42 (10th October 2019) - Huang, Chao; Zhu, Kaifang; Zhang, Yingying; Lu, Guizhen; Shao, Zhichao; Gao, Kuan; Mi, Liwei; Hou, Hongwei
Abstract : Nanoscale 1 and 2 with the benefit of readily accessible active sites had shown to be more effective heterogeneous catalysts than large sizes of 1 and 2 to execute tandem conversion reactions of nitromethylbenzenes into benzolic acids frameworks. Abstract : Precise control over the morphology and size of coordination polymers (CPs) is crucial for extending these inorganic–organic materials to many advanced applications, in particular for heterogeneous catalysis. In this work, two Zn-based CPs, {[Zn3 (idbt)2 (4, 4′-dmbpy)2 ]·H2 O} n (1 ) and {[Zn3 (idbt)2 (H2 O)3 ]·H2 O} n (2 ) (H3 idbt = 5, 5′-(1 H -imidazole-4, 5-diyl)-bis-(2 H -tetrazole), 4, 4′-dmbpy = 4, 4′′-dimethyl-2, 2′-bipyridine), were synthesized through solvothermal reactions. The morphologies and particle sizes of 1 and 2 could be controlled from large scale to nanoscale by regulating the amount of poly(vinyl alcohol) (PVA). Furthermore, for the conversion reactions of nitromethylbenzenes into benzoic acids, the catalytic properties of nanoscale 1 and 2 were much more efficient than those of large size of 1 and 2, because of the benefit of readily accessible active sites in the nanoscale sized particles, which provide a tunable and functionalizable platform for the conversion reaction by minimizing the diffusion distance but do little for the selectivity.